The genetic background modulates the intensity of Rpv3‐dependent downy mildew resistance in grapevine. (25th February 2018) - Foria, Serena; Magris, Gabriele; Morgante, Michele; Di Gaspero, Gabriele
Abstract: Grape varieties with resistance to downy mildew (DM) carry alien chromosome segments in Vitis vinifera backgrounds. We previously showed that the largest descent group shares a non‐ vinifera haplotype at the locus Rpv3 . Here, we performed a common garden experiment with 76 varieties to evaluate the level of field resistance across four years. All varieties exhibited effector‐triggered immunity (ETI)‐associated necrosis. On a scale of 1–9, the median OIV452 value for foliar resistance was 7.1 in the resistant lineage vs. 3.2 in vinifera controls. Genotype, year and their interaction significantly affected the level of resistance. Some resistant genotypes showed high mean values of OIV452 and low variance among years. Other resistant genotypes showed lower mean OIV452 and higher variance. They were capable of activating ETI, but the intensity was inadequate to restrict pathogen growth under highly conducive conditions. Rpv3 ‐dependent responses were stronger in highly native genetic backgrounds and tended to attenuate in late backcross generations. Genetic backgrounds donated by European winegrapes of the convarietas occidentalis provided on average higher levels of Rpv3 resistance than backgrounds of orientalis table grapes.